The EDUCATIONAL BARRIERS TO PRO-ENVIRONMENTAL BEHAVIOR: AN ANALYSIS OF INHIBITING FACTORS - Nurul Hidayati Ahmad; Sigit Nugroho; Syarifah Farradinna; Icha Herawati (Curricula: Journal of Teaching and Learning, 2023)
This research delves into the inhibiting factors of pro-environmental behavior in Indonesia, with a particular emphasis on waste management challenges in Pekanbaru, a major contributor to Riau's waste production. It examines the gap between environmental knowledge and action, attributing the lack of pro-environmental behavior to insufficient environmental education and exploring the cognitive aspects of littering behavior through the lens of Social Learning Theory. Employing a descriptive qualitative methodology, the study gathers data via interviews and observations, analyzing it through techniques of data reduction, display, and verification to identify key themes from 3 participants. These themes encompass individual factors such as awareness, knowledge, and attitudes; behavioral factors including practicality, intention, and lifestyle; and environmental factors like social pressure and result orientation, particularly within the Conservation lifestyle type. The research underscores the complex interplay of these factors in shaping pro-environmental behavior and suggests that future research should target behavioral changes that encourage pro-environmental outcomes. Acknowledging the contributions of the Islamic University of Riau and its participants, the study offers a foundation for further exploration in the field of environmental behavior.